Fertilidade do solo,aspectos fisiológicos e produtivos de Morinda citrifolia L. sob consórcio, cobertura e biofertilizante em manejo agroecológico - Coaracy, Thiago do Nascimento (2023)
The cultivation of noni has been gaining ground in the Brazilian Northeast in areas for experimental purposes and in domestic cultivation, as its fruit is considered a powerful natural antioxidant. Studies related to nutritional requirements are of great importance for a good development and monitoring of this fruit tree. Despite the rusticity of noni in adverse edaphoclimatic conditions, research directed at soil quality, production and physiology are essential for good management of this crop. This research aimed to evaluate soil quality, production, and physiology in noni plants under different cultural managements. In conducting the experiment, a randomized block design was used, in a factorial scheme (2×2×4), referring to noni with and without intercropping with banana cultivar Prata , without and with vegetation cover, and four levels of bovine manure biofertilizer , totaling 16 treatments. The research was carried out from February to November 2019, in an experimental area in the field with dimensions of 40 m × 70 m, equivalent to an area of 2,800 m², located in the Agriculture Sector of the Center for Human, Social and Agrarian Sciences, Campus III, of the Federal University of Paraíba, municipality of Solânea, Paraíba. Field analyzes were carried out regarding parameters of soil quality, physiology and fruit production of noni plants intercropped with banana trees, vegetation cover and biofertilizer.